PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING KELAS V SD SUBSIDI BUDI RAHAYU SAMBIREJO TIMUR T.A 2020/2021 - Syahfitri Nila Suari; Tri Astari (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2020)
This study investigates the improvement of mathematics learning outcomes among fifth-grade students at SD Subsidi Budi Rahayu Sambirejo Timur through the application of the Student Facilitator and Explaining (SFE) learning model. This model allows students to solve problems through discussion and subsequently communicate their acquired knowledge to their peers within the group. The research method employed involves providing students the freedom to experiment by presenting learning materials to their group members and communicating their discussion results to the class. The findings indicate that prior to the implementation of the SFE model, the average student score was 49.83, with 23 students (76.67%) not achieving the passing grade. After applying the SFE model in the first cycle, the average score improved to 65.83, with 16 students (53.33%) achieving the passing grade, while 14 students (46.67%) did not pass. However, learning in the first cycle was not optimal as many students still did not reach the passing grade, and student participation remained low. In the second cycle, after instructional improvements, there was a further increase in the average score to 74.50, with 25 students (83.33%) achieving the passing grade, while 5 students (16.67%) did not pass. These results demonstrate that the SFE model effectively enhances students' learning outcomes from the initial state to the post-implementation state.